2010
DOI: 10.1111/j.1468-3083.2009.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate as a prognostic factor in localized invasive cutaneous melanoma

Abstract: The GR of localized cutaneous melanomas may be a possible prognostic factor for survival. Additionally, rapid GR is associated with male patients more advanced in age at diagnosis, which suggests the need to assess new strategies for the early detection of these melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 22 publications
(30 reference statements)
3
28
0
Order By: Relevance
“…Our results are in agreement with previous studies showing that GR is an independent prognostic indicator for overall survival even after adjustment for tumor mitotic rate, Breslow, and ulceration [1,2,7]. Interestingly, we have replicated the findings of previous studies showing a survival benefit in patients with selfreported GR of less than 0.4 mm/month [2,8].…”
supporting
confidence: 95%
See 2 more Smart Citations
“…Our results are in agreement with previous studies showing that GR is an independent prognostic indicator for overall survival even after adjustment for tumor mitotic rate, Breslow, and ulceration [1,2,7]. Interestingly, we have replicated the findings of previous studies showing a survival benefit in patients with selfreported GR of less than 0.4 mm/month [2,8].…”
supporting
confidence: 95%
“…Whether this represents a distinct pattern of melanoma growing in patients with different patterns of sun exposure and probably different phenotypic characteristics should be further investigated. Compared with other studies [1][2][3]7] a very significant proportion of participants were excluded, because of their inability to recall tumor growth. It is possible that our population is less sensitized and aware about skin cancer and the alarming changes on a mole.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Breslow thickness of MMs can increase between 0.05 to 0.5 mm every month, depending on the type of tumour (15,16). A recent study showed that MMs triaged via TD were on average 1.06 mm in thickness as compared to 1.64 mm in patients who received care after traditional paper referral (17).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, these three histological types together accounted for more than 20% of all melanomas and were characterized by a significantly higher thickness as compared to the ‘superficial spreading’ and ‘lentigo maligna’ types. This could result both from a more aggressive clinical behaviour of these histologic types 29 and from later recognition of such tumours, which are often amelanotic and/or very different from the classical aspect of a ‘beauty spot’. These forms of melanoma are particularly prone to be unrecognized using classical messages concerning melanoma, like the ABCD rule 30 .…”
Section: Discussionmentioning
confidence: 99%